Navigating public, semi-public, and private drug use environments: A qualitative examination of unsheltered homelessness and drug use in Baltimore City - Ashley Q. Truong; Bridget Duffy; Haneefa T. Saleem; Jessie Chien; Gregory D. Kirk; Shruti H. Mehta; Becky L. Genberg; Sabriya L. Linton (PLoS ONE, 2025)
Unsheltered people experiencing homelessness (PEH) in the United States (US) have a disproportionately high burden of illegal drug use and overdose. Due to their economic and social marginalization, unsheltered PEH who use drugs are often constrained in where they use drugs, and this can hinder their engagement in harm reduction practices and increase their overdose risk. Using interpretative phenomenological analysis, this study investigates how unsheltered PEH who use drugs in Baltimore City perceive and engage with their drug use environment and how public, semi-public, and private features of their environment influence drug use practices and overdose risk. Public settings (e.g., street) are accessible to the general public, while semi-public settings (e.g., library restrooms) provide public access with some restrictions. In contrast, private settings (e.g., private residence) are under private ownership with no public access. Participants were recruited from the AIDS Linked to Intravenous Experience (ALIVE) Study. Data was analyzed from interviews conducted with nine participants. Participants described complex experiences managing their drug use in public, semi-public, and private spaces. In public and semi-public spaces, participants engaged in varied strategies to seek privacy. Privacy in these spaces provided participants a sense of refuge from policing and interference, but in some instances, at the expense of drug use safety. To access private spaces for drug use and shelter, participants reported engaging in an informal economy of sharing drugs and other resources. Using in private spaces enhanced participants’ sense of comfort and enabled safer drug use practices, though access to these spaces was inconsistent. A building where people can use drugs safely and privately with supervision from peers and medical staff was commonly described as an ideal drug use space across participants. Findings highlight the need to identify resources and interventions to facilitate safer drug use for unsheltered PEH who use drugs in the US. Future interventions should take a multi-level, harm reduction approach, targeting contextual and individual factors to promote safer drug use and minimize the risk of drug use-related harms among unsheltered PEH.